SPE Annual Technical Conference and Exhibition 1988
DOI: 10.2118/18076-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Transition Metals Salt Solutions as Additives in Steam Recovery Processes

Abstract: => -c =-t q In ** q-c t*8t8 , howevu , ahanges am mare pronouwod in ehortu rcaation tbao. It is well doaumatod by laboratoryqnd fhld data In on. oaso tlm oil viscogitywas lowered 20 tithat be8idoB phyaieal ohargu suah qm viwomity mm q reduotionwith tqraturo apd qteu mutilation, the atom injoatiompromana arm q campanied by INTROWCTIOM ohmiacl reaotionswhich, qs it haa been the aaea in tha M-6 staaa &Lve proj9ctin the BolivasCoast 8toaa h jwt%on proaeu.s, both cyolic and drive, of IA. Maracaibo, produco large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…However, further research results showed that aquathermolysis has little effect on extra-heavy oil only in the presence of the injection steam (Fan and Liu, 2001). Because the aquathermolysis of extra-heavy oil can regress rapidly, a large number of scientists conducted a lot of researches on various catalysts in order to catalyze the aquathermolysis (Rivas et al, 1988;Clough, 1989;Campos and Hernandez, 1994;Strausz et al, 1999;Babcock and Morrell, 2001;Fan and Liu, 2001;Chen et al, 2005;Jing et al, 2007). By catalytic aquathermolysis, more heavy components pyrolyzed and the structure had been changed, these changes could hardly regress and eventually lead to the reduction of the viscosity of heavy oil, thereby benefiting the oil exploitation, transportation, and upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…However, further research results showed that aquathermolysis has little effect on extra-heavy oil only in the presence of the injection steam (Fan and Liu, 2001). Because the aquathermolysis of extra-heavy oil can regress rapidly, a large number of scientists conducted a lot of researches on various catalysts in order to catalyze the aquathermolysis (Rivas et al, 1988;Clough, 1989;Campos and Hernandez, 1994;Strausz et al, 1999;Babcock and Morrell, 2001;Fan and Liu, 2001;Chen et al, 2005;Jing et al, 2007). By catalytic aquathermolysis, more heavy components pyrolyzed and the structure had been changed, these changes could hardly regress and eventually lead to the reduction of the viscosity of heavy oil, thereby benefiting the oil exploitation, transportation, and upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the injection steam can not only reduced the viscosity of heavy oil but also reacted with some components of the heavy oil and of the reservoir minerals, and the properties and compositions of the heavy oil were changed [4][5][6]. Subsequently, scientists studied the aquathermolysis further, they added various catalysts to catalyze the aquathermolysis [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Upon catalytic aquathermolysis, more heavy components of the heavy oil pyrolyzed and the structure changed to a larger degree, especially some heteroatom containing structure, and these changes could hardly regress and eventually lead to the reduction of the viscosity of heavy oil, thereby benefiting the oil exploitation, transportation and upgrading.…”
Section: Introducationmentioning
confidence: 99%
“…Firstly, Hyne et al studied the metal ions of Ni 2+ 、Fe 2+ 、Cu 2+ 、Zn 2+ and so on as catalyst, then pointed out that the percentage of saturate、aromatic increased and resin、asphalt and S decreased after the catalytic aquathermolysis [7]. Rivas et al studied the nickel salt as additive under aqueous and thermal conditions, and found that viscosity of heavy oil decreased and the quantity of H 2 、CO 2 and C 2+ increased after the reaction [8]. Clark et al used Fe ( II) as additive, and found it accelerated the cleavage of the C-S bonds [9].…”
Section: Introducationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several routes for underground crude oil upgrading have been reported. These concepts involve the following: Downhole steam distillation 1 , deasphalting [2][3][4][5] , underground visbreaking [6][7][8][9] , hydrogen [10][11][12][13][14][15][16][17] or hydrogen precursor injection [18][19][20][21][22] and in situ combustion [23][24][25] . With the exemption of the later route, the numerical simulation of downhole upgrading processes has been relatively less studied.…”
Section: Introductionmentioning
confidence: 99%